Сathode design effect on gas breakdown and modes of burning of the glow discharge in nitrogen - Lisovskiy, V.A.; Osmayev, R.O.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2018)
This paper reports the breakdown curves and current-voltage characteristics we have measured for the discharge
in the dc electric field. It has been found that almost all breakdown curves measured for cathodes of different design
(cylindrical one, two stepped cathodes, conical, spherical and pin ones) practically coincide with the curve for the
gap value of 5 mm between flat electrodes near to and to the right of the minimum, excluding the sections for conical and pin cathodes within the gas pressure range above 10 Torr. Left-hand branches of breakdown curves diverge
somewhat but they still behave themselves as a family of close curves. At low gas pressure the discharge is burning
only in the abnormal mode with the smallest current observed with the pin cathode whereas the largest current occurs with the spherical one. At large pressure the normal mode is observed in the broad current range with the spherical and step cathodes and it is almost not seen with the pin one. Виміряні криві запалювання і вольт-амперні характеристики розряду в постійному електричному полі.
Майже всі криві запалювання, виміряні для катодів різної форми (циліндричної, двоступінчастої, конічної,
сферичної та штирьової), практично співпадають з кривою для проміжку 5 мм між плоскими електродами
поблизу і праворуч від мінімуму, за винятком ділянок для конічного і штирьового катодів у діапазоні тиску
вище 10 Торр. Ліві гілки кривих запалювання дещо розходяться, але ведуть себе як сімейство близьких кривих. При низькому тиску газу розряд горить тільки в аномальному режимі з найменшим струмом на штирьовому і найбільшим струмом на сферичному катоді. При високому тиску нормальний режим спостерігається в широкому діапазоні значень струму для сферичного та ступінчастого катодів і його майже не видно
для штирьового катоду. Измерены кривые зажигания и вольт-амперные характеристики разряда в постоянном электрическом поле. Почти все кривые зажигания, измеренные для катодов различной формы (цилиндрической, двухступенчатой, конической, сферической и штыревой), практически совпадают с кривой для зазора 5 мм между
плоскими электродами вблизи и справа от минимума, за исключением участков для конического и штыревого катодов в диапазоне давлений выше 10 Торр. Левые ветви кривых зажигания несколько расходятся, но
ведут себя как семейство близких кривых. При низких давлениях газа разряд горит только в аномальном
режиме с наименьшим током на штыревом и наибольшим током на сферическом катоде. При больших давлениях нормальный режим наблюдается в широком диапазоне токов для сферического и ступенчатого катодов и почти не виден для штыревого катода.